2013
DOI: 10.1016/j.sleep.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral parent training to address sleep disturbances in young children with autism spectrum disorder: a pilot trial

Abstract: Objectives A large percentage of children with autism spectrum disorders (ASD) have bedtime and sleep disturbances. However, the treatment of these disturbances has been understudied. The purpose of our study was to develop a manualized behavioral parent training (BPT) program for parents of young children with ASD and sleep disturbances and to test the feasibility, fidelity, and initial efficacy of the treatment in a small randomized controlled trial (RCT). Participants and methods Parents of a sample of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 65 publications
(75 reference statements)
1
101
0
2
Order By: Relevance
“…All RCTs were assessed as having high risk of bias for most items on the Cochrane Risk of Bias tool because of issues with randomization and incomplete outcome data. We were unable to find a registered protocol for 10 RCTs, and in all RCTs blinded outcome assessment was either not undertaken or it was unclear whether blinding had occurred . However, we do note that the type of interventions and outcomes under investigation make robust, blinded outcome assessment challenging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All RCTs were assessed as having high risk of bias for most items on the Cochrane Risk of Bias tool because of issues with randomization and incomplete outcome data. We were unable to find a registered protocol for 10 RCTs, and in all RCTs blinded outcome assessment was either not undertaken or it was unclear whether blinding had occurred . However, we do note that the type of interventions and outcomes under investigation make robust, blinded outcome assessment challenging.…”
Section: Resultsmentioning
confidence: 99%
“…For the RCTs that were comparing parent‐directed interventions in terms of mode of delivery or intensity of support, the evaluation question is different and is concerned with comparing the effectiveness of alternative (in the case of this review, more and less resource intensive) ways of providing an intervention . In three of these trials, no significant differences in outcomes, as assessed by CHSQ scores and/or SOL, were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Schreck and Mulick (2000) found that parents of children with ASD reported comparable amounts of sleep in their children when compared to controls but endorsed higher rates of sleep problems. Additionally, behaviorally focused treatments have been effective in reducing parent reports of sleep problems but these changes did not always coincide with actigraphically-measured changes in sleep behavior (Johnson et al, 2013). …”
Section: Syndrome/condition Specific Sleep Problemsmentioning
confidence: 99%
“…In typically developing children, behavioral sleep intervention has demonstrated efficacy and effectiveness in treating BSD 24,25 . In addition, a number of preliminary small sample studies have demonstrated that behavioral interventions are promising among children with intellectual and developmental disabilities (IDD) 2628 . To date, however, there is a lack of empirical support for use of behavioral insomnia treatment among children with DS 2931 .…”
mentioning
confidence: 99%